Empowerment through contract farming partnership facilitation in cavendish banana agribusiness in support of sustainable agriculture - Andi Danata AR (Community Service for Sustainable Community Journal, 2026)
Background: Contract farming has been widely recognized as a mechanism for improving smallholder farmers’ productivity, market access, and income stability. However, existing studies generally examine Contract Farming, Creating Shared Value (CSV), and Asset Based Community Development (ABCD) separately, resulting in limited understanding of how these approaches can be integrated within sustainable agribusiness partnerships. This study analyzes the implementation of community empowerment in Cavendish banana agribusiness through a cooperative-based contract farming model integrating CSV and ABCD principles. Method: A mixed method case study approach was employed involving 458 farmers affiliated with the Bina Sejahtera Cooperative in Pesawaran Regency, Indonesia. Data were collected through structured interviews, focus group discussions, field observations, and institutional documentation. Quantitative data were analyzed using descriptive comparative analysis based on before–after program indicators, while qualitative data were examined through thematic analysis to explore empowerment processes, partnership dynamics, and institutional development. Findings: The results indicate that the integration of CSV and ABCD within the contract farming system generated significant socio-economic and institutional benefits. Farmer productivity increased from 18–20 to 22–24 tons/ha/year (+15–20%), while seasonal income rose from IDR 18–22 million to IDR 23–28 million (+20–25%). Market access expanded from local traders to cooperative-based and export-oriented channels, reducing dependence on intermediaries and improving price stability. In addition, cooperative participation increased from 55% to 80% of active members, while adoption of Good Agricultural Practices (GAP) improved from 40% to 715%. Conclusion: These outcomes demonstrate enhanced farmer capacity, stronger institutional performance, and improved agribusiness sustainability. Novelty/Originality of this article: This study proposes an integrative framework that combines CSV and ABCD within a cooperative-based contract farming system. The model demonstrates how market-oriented value creation and asset-based community empowerment can be simultaneously implemented to generate measurable economic, social, and institutional impacts, offering a replicable approach for inclusive and sustainable agribusiness development.